PKM Upaya Peningkatan Pemahaman Guru-Guru Akuntansi Sekolah Menengah Kejuruan Terhadap Materi Akuntansi Desa - Vita Fitria Sari; Dewi Febriyani; Mayar Afriyenti (Wahana Riset Akuntansi, 2019)
Since the issuance of the 2013 revised curriculum in 2018 it has become a challenge for education including teachers. Teacher professionalism becomes a question in relation to the implementation of the 2013 revised 2018 curriculum. For Vocational High School teachers, for the content of vocational specialization in business and management, especially in accounting and financial institutions, there has been a change in the expertise competency section, one of the most stealing changes attention is the emergence of subjects "accounting practicum institutions / government agencies" which will be taught in class XI and XII. Government accounting is a field of accounting that has never been included in the Vocational High School curriculum, therefore accounting teachers at the Vocational High School are totally blind or unfamiliar with this field. Even though it is still in the same family with government accounting, village accounting has a different dimension to government accounting material, therefore efforts are needed to increase teacher understanding of village accounting materials. The subject "village accounting practicum" will be taught in the 2019/2020 school year for class XII. This study aims to look at teacher readiness and identify efforts that can be used in improving teacher understanding of village accounting. The results of this study indicate that the readiness of teachers in teaching subjects "village accounting practicum" is still limited even though these subjects will be taught in the 2019/2020 school year. Therefore capacity building and workshop can be used as an effort to increase the understanding of accounting teachers in village accounting materialsKeywords: capacity building, professionalism, village accounting, vocational teachers, workshop